APPLICATION OF CHAOTIC DYNAMICAL SYSTEMS IN ROBOTICS - U. A. Sychou (Informatika)
An overview of modern directions of research in the field of chaotic dynamics is provided. The results of the research can be used for the control of mobile robots. There are such directions of research as stabilization of nonlinear dynamical systems with chaotic dynamics, generation of chaotic vibrations and their applications in information processing. The tasks of mobile robots control that allow to increase functionality and autonomy of robots operating in non-deterministic environment are formulated.